PENGARUH BAURAN PEMASARAN, DAN ORIENTASI PASAR TERHADAP KEUNGGULAN BERSAING DALAM MENINGKATKAN KINERJA PEMASARAN PADA PERUSAHAAN BATIK DI SURAKARTA - Fatonah, Siti (Program Doktor Ilmu Ekonomi, 2009)
Marketing management is a process of management. Marketing is various theoretical approaches were developed based on the empirical facts in order to arising a concept regarding the reference of action at practical level or operational and managerial level. The series of management activities, marketing management could be seen as company’s effort in dealing with more competitive global competition. Those efforts were conducted by the companies in dealing with competition through the application of marketing strategy, combined with competitive advantage strategy, as well as batik industry at Surakarta, Central Java.The growth of batik industry which is getting tighter in the middle of the various type of batik of the world, batik Indonesia has not yet losing its characteristics. Even batik of Central Java which is consider to have the richest design is still possessing its soul/spirit. Nevertheless, as neighboring countries are rapidly promoting their batik’s products through various continents, batik of Indonesia seemed made no further progress (stay still). Batik which is wear as daily clothing recently is indeed print out with batik’s motif/design. There is indeed an enlightening development in a matter of batik’s consumption nowadays. If batik was only used for certain events, today, its region of utilization has became more broaden. Batik is also often modified with other motif / design for daily clothing. Along with the times, batik is also squirming. Its fabrics is presenting with its latest design.From the result of the test toward the model within this research, using estimation of Maximum Likelihood Estimation (ML), analysis of Structural Equation Model (SEM), and the assistance of Amos 6 software toward 200 respondents of batik entrepreneurs at Surakarta, it is able to provide the explanation regarding the influence of marketing diffusion and marketing orientation toward competitive advantage in developing/increasing market performance at batik’s companies at Surakarta.Within this research, the result obtained from marketing strategy (Products, Price, Promotion, and Distribution), and Marketing Orientation, providing positive influence toward Competitive advantage with the value of first Determination Coefficients (R2) is equal to 0,841, it shows that by using marketing strategy and maximum marketing orientation, it could increase company’s competitive advantage of batik’s companies at Surakarta as much as 84,1%, the value of second Determination Coefficient (R2) is equal to 0,791, which means that by marketing strategy, marketing orientation and high competitive advantage could increase the performance of batik’s company at Surakarta as much as 79,1%.Key words : Marketing strategy, Marketing Orientation, Competitive Advantage, Marketing Performance